2016
DOI: 10.1108/bfj-11-2015-0445
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status as a determinant of cognitive development among preschool children in South-Western Nigeria

Abstract: Purpose – Improving the health of children under the age of five is one of the main objectives of primary healthcare services in most developing countries. The purpose of this paper is to identify the nutritional status of children under the age of five and its impact on cognitive function. Design/methodology/approach – The cross-sectional study was carried out in a semi-urban community in south-western Nigeria. The sample consisted of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Eventhough, one growth-stunted child had below-average VIQ and FSIQ, with a history of high levels of stimulation from the environment, the child's cognitive function was not as poor as children in other study. 26 We found a positive correlation between stimulation and general cognitive function in normalheight children. Although the correlation was weak and the effect was small, it shows that stimulation can influence cognitive function.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Eventhough, one growth-stunted child had below-average VIQ and FSIQ, with a history of high levels of stimulation from the environment, the child's cognitive function was not as poor as children in other study. 26 We found a positive correlation between stimulation and general cognitive function in normalheight children. Although the correlation was weak and the effect was small, it shows that stimulation can influence cognitive function.…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, a previous study showed that 16.7% of short-stature children diagnosed with stunted growth had poor cognitive status. 26 This difference was probably because most of our shortstature subjects were diagnosed as normal variants, leaving a small sample size of growth-stunted children (2 subjects).…”
Section: Discussionmentioning
confidence: 99%
“…Semakin lama tahun pendidikan Ibu,maka peluang anak untuk mempunyai kognitif tinggi semakin meningkat. Hasil ini sejalan dengan penelitian (Puspitasari, Sudargo & Gamayanti, (2011), Warsito et al (2012), dan Onifade, Otegbayo, Akinyemi, Oyedele, & Akinlade (2016). Hal tersebut dapat disebabkan karena Ibu yang berpendidikan tinggi lebih terbuka terhadap hal-hal baru dan informasi yang bermanfaat dari berbagai media, sehingga memiliki pemahaman lebih baik perihal perkembangan anak.…”
Section: Kecenderunganunclassified
“…In simple terms, stunting is the phenomenon of failure of a child's physical development due to malnutrition experienced by infants under five years or while still in the womb. Stunting, which has an impact on children's physical and cognitive growth [3], in the long run will affect the future of a nation in many sectors. People who grow short, of course, will have different physical abilities from residents of normal height.…”
Section: Introductionmentioning
confidence: 99%